Integration of macromolecular complex data into the Saccharomyces Genome Database. (4th February 2019) - Wong, Edith D; Skrzypek, Marek S; Weng, Shuai; Binkley, Gail; Meldal, Birgit H M; Perfetto, Livia; Orchard, Sandra E; Engel, Stacia R; Cherry, J Michael; ,
Abstract: Proteins seldom function individually. Instead, they interact with other proteins or nucleic acids to form stable macromolecular complexes that play key roles in important cellular processes and pathways. One of the goals of Saccharomyces Genome Database (SGD;www.yeastgenome.org ) is to provide a complete picture of budding yeast biological processes. To this end, we have collaborated with the Molecular Interactions team that provides the Complex Portal database at EMBL-EBI to manually curate the complete yeast complexome. These data, from a total of 589 complexes, were previously available only in SGD's YeastMine data warehouse (yeastmine.yeastgenome.org ) and the Complex Portal (www.ebi.ac.uk/complexportal ). We have now incorporated these macromolecular complex data into the SGD core database and designed complex-specific reports to make these data easily available to researchers. These web pages contain referenced summaries focused on the composition and function of individual complexes. In addition, detailed information about how subunits interact within the complex, their stoichiometry and the physical structure are displayed when such information is available. Finally, we generate network diagrams displaying subunits and Gene Ontology annotations that are shared between complexes. Information on macromolecular complexes will continue to be updated in collaboration with the Complex Portal team and curated as more data become available.